Toward a conceptual framework of hyporheic exchange across spatial scales - Magliozzi, Chiara; Grabowski, Robert C.; Packman, Aaron I.; Krause, Stefan (European Geosciences Union (EGU) / Copernicus Publications, 2018)
Rivers are not isolated systems but interact continuously with groundwater from their confined headwaters to their wide lowland floodplains. In the last few decades, research on the hyporheic zone (HZ) has increased appreciation of the hydrological importance and ecological significance of connected river and groundwater systems. While recent studies have investigated hydrological, biogeochemical and ecohydrological processes in the HZ at bedform and reach scales, a comprehensive understanding of process-based interactions between factors operating at different spatial and temporal scales driving hyporheic exchange flows (HEFs) at reach scale and larger is still missing. Therefore, this review summarizes the factors and processes at catchment, valley, and reach scales that interact to control spatial and temporal variations in hyporheic exchange flows. By using a multi-scale perspective, this review connects field observations and modelling studies to identify the process driving patterns and dynamics of HEF. Finally, the influence of process interactions over multiple spatial scales is illustrated in a case study, supported by new GIS analyses, which highlights the importance of valley-scale factors to the expression of HEF at the reach scale. This conceptual framework will aid the development of approaches to interpret hyporheic exchange across scales, infer scaling relationships, and inform catchment management decisions.